Penerapan layanan perpustakaan di Open Library Telkom University - Repa Ruhya Try Atmadja (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2026)
Universitas Pendidikan Indonesia, as one of the Lembaga Pendidikan Tenaga Kependidikan (LPTK), continuously strives to improve quality, efficiency, and relevance by developing the Tri Dharma of Higher Education. To bridge this gap, UPI offers an internship program that helps students prepare for entering the workforce. This internship program aims to provide direct field experience. This service is implemented through the Program Penguatan Profesi Kepustakaan Non-Kependidikan (P3KNK) at the Telkom University Open Library. Interns are assigned to circulation services, library materials processing, and reference services. Each section provides experience and hones different skills. The internship at the Telkom University Open Library provides interns with an opportunity to broaden their insights and apply the knowledge they have acquired during their studies. In this case, interns divide the tasks they undertake according to their competencies and abilities, with the main goal of developing their competencies, especially in librarianship.